The Implementation of Green Practices to improve the service quality of front office at K Club Ubud - Ni Nyoman Angelica Kerta Dewi; Darlina, Lien; Nadra, Nyoman Mastiani; Chaerunnisah, Indah Utami; Sang Ayu Made Krisna Dewi Natalia; Ge Xiaoling (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
The K Club Ubud in Gianyar, Bali, has used green practises to enhance the front office department's service quality. The goal of this study is to examine these activities and identify the green practises indicators that must be maintained and improved. Questionnaires, interviews, observations, and documentation were used to collect data for this study. The sample strategy used in this investigation was simple random sampling. In order to collect data, online surveys are distributed to respondents. As part of the processing, the questionnaire was subjected to validity and reliability tests. The servqual test (quality of service) and importance-performance analysis (IPA) are then employed as data analysis techniques in this study. According to the findings of this study, the application of green practices has been done in an optimal manner, as evidenced by the outcomes of the application of 3R activities. The results of the servqual test, which show that the front office department at K Club Ubud has seven gaps (+) and one gap (-) in the form of eight question indicators, can be used to describe how successfully green practices have been implemented. According to the importance performance analysis (IPA) results, the front office department must maintain the quality of the services for one indication while making improvements for the other.